2020
DOI: 10.1021/acsanm.0c01747
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Studies of Si2BN Nanosheets as Anode Materials for Magnesium-Ion Batteries

Abstract: The unique structural characteristics make the 2D materials potential candidates for designing negative electrodes for rechargeable energy storage devices. Here, by employing density functional theory (DFT) calculations, we study the precise viability of using Si 2 BN, a graphene-like 2D material, as a high-capacity anode material for Mg-ion battery (MIB) application. The favorable Mg-adsorption sites with maximum possible coverage effect are explored in detail. It is found that the Si 2 BN sheet can be adsorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 72 publications
4
43
0
Order By: Relevance
“…LIBs represent the most stable, reliable, and widely used form of electrochemical energy-storage devices for mobility (electric vehicles) and portable electronics as they possesses high values for energy and power density. , However, the limited abundance, fabrication cost, environmental hazards, and most importantly, safety issues, such as thermal runaway and explosion due to dendrite formation, are the major limiting factors of the LIBs. ,, All these limitations suggest the need for an alternative to Li-ion technology with an improved battery-related matrix and environmental benignity. Hence, there has been a growing interest toward other monovalent and multivalent metal-ion batteries such as Na, , K, Mg, Ca, and Al. …”
Section: Introductionmentioning
confidence: 99%
“…LIBs represent the most stable, reliable, and widely used form of electrochemical energy-storage devices for mobility (electric vehicles) and portable electronics as they possesses high values for energy and power density. , However, the limited abundance, fabrication cost, environmental hazards, and most importantly, safety issues, such as thermal runaway and explosion due to dendrite formation, are the major limiting factors of the LIBs. ,, All these limitations suggest the need for an alternative to Li-ion technology with an improved battery-related matrix and environmental benignity. Hence, there has been a growing interest toward other monovalent and multivalent metal-ion batteries such as Na, , K, Mg, Ca, and Al. …”
Section: Introductionmentioning
confidence: 99%
“…Although in terms of capacity, T-type or H-type Mo 2 B has no great advantage as a negative electrode material for Mg-ion batteries, the capacity is not low compared with the currently reported theoretical capacity of negative electrode materials for Mg-ion batteries. For example, Si 2 BN previously reported by Panigrah as a negative electrode material for Mg-ion batteries has a theoretical capacity of 647.896 mA h g −1 [48]. Fan et al calculated that Mo 2 C used as a negative electrode material for Mg-ion batteries has a theoretical capacity of 469.79 mA h g −1 [49].…”
Section: Theoretical Storage Capacities Of Mg Atoms On Mo 2 B and Ave...mentioning
confidence: 99%
“…Due to its exceptional structure and properties, the Si 2 BN-ML exhibits prospective applications beyond those of graphenes, and it has generated ample interest among the scientific community. Studies reported that the Si 2 BN-ML is suitable for the anode applications of Li-ion, Na-ion and Mg-ion batteries, 27,28 hydrogen storage, 29,30 etc. In 2018, by employing time-dependent density functional theory (TDDFT) calculations, Yuan et al investigated the optoelectronic and photosensitive detector applications of Si 2 BN nanostructures and their hybrids.…”
Section: Introductionmentioning
confidence: 99%